Agricultural change in Copper Age Croatia (ca. 4500–2500 cal B.C)? - Reed, K (Springer, 2016)
The Copper Age in the Carpathian Basin is marked by a distinct change in settlement patterns, material culture, social traditions and subsistence practices; however, few studies address the nature of crop cultivation in the region. This paper examines new archaeobotanical data from 13 Copper Age (ca. 4500–2500 cal BC) sites located in continental Croatia, in order to assess the extent to which crop agriculture may have changed and contributed to overall subsistence economies in the Copper Age. From the archaeobotanical results, a dominance in einkorn and emmer is seen followed by barley. Less frequently millet, naked wheat and spelt/new glume wheat are also recovered, but due to their limited numbers, it is less clear whether they were grown as crops or represent weeds. Pulses (e.g. lentil, pea and grass pea), fruit remains (e.g. cornelian cherry and chinese lantern) and wild plant and weed species are also recovered, although more commonly from the late Copper Age sites. The archaeobotanical results show a clear reduction in the quantity and range of plant species recovered during the early/middle Copper Age; however, this is likely the result of taphonomic bias rather than a reduction in crop cultivation. The results therefore highlight problems of recovery bias in the region, which makes comparisons between sites as well as the reconstruction of crop husbandry regimes difficult. Overall, the results from continental Croatia suggest that the type of crops cultivated continued relatively unchanged from the late Neolithic, although it is clear that more research is desperately needed to explore the relationship between crop agriculture and the changing socio-economic environment of the Copper Age in the region.